Orientasi Perkembangan Pendidikan Islam Pasca Proklamasi Indonesia - Fauzi Fahmi; Firmansyah Firmansyah (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2021)
History revealed that Islamic education in Indonesia has its characteristics and plays a vital role in advancing Islamic culture in Indonesia. This study used a library research method that relies on sources from books and articles in scientific journals. The results showed that after the proclamation, there are four types of Islamic education in Indonesia, i.e., Madrasah, Islamic boarding schools, Public Schools, and Islamic schools. The development of Islamic in Indonesia as a revival, renewal, and enlightenment. The Islamic education system that existed at that time had developed as an effort of implementing Islamic law, so it guarantees and opportunities to continue to exist and develop.